1997
DOI: 10.1086/304113
|View full text |Cite
|
Sign up to set email alerts
|

Optical Substructures in 48 Galaxy Clusters: New Insights from a Multiscale Analysis

Abstract: We analyze the presence of substructures in a set of 48 galaxy clusters by using galaxy positions and redshifts. The data are taken from literature sources, with the addition of some new data provided by recent observations of galaxy clusters. We use a multiscale analysis that couples kinematical estimators with the wavelet transform. With respect to previous works, we introduce three new kinematical estimators. These estimators parameterize the departures of the local means and/or local dispersions of the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 106 publications
7
117
2
Order By: Relevance
“…Our values of and D are typical of groups of galaxies. Nevertheless, the average extensions of our groups are larger than those derived by Girardi et al 1997 ($0.2 h À1 Mpc). The KMM technique for substructure detection tends to identify systems at larger distances from the cluster center (DV = 1515 AE 304 km s À1 ).…”
Section: Substructure Propertiescontrasting
confidence: 75%
See 1 more Smart Citation
“…Our values of and D are typical of groups of galaxies. Nevertheless, the average extensions of our groups are larger than those derived by Girardi et al 1997 ($0.2 h À1 Mpc). The KMM technique for substructure detection tends to identify systems at larger distances from the cluster center (DV = 1515 AE 304 km s À1 ).…”
Section: Substructure Propertiescontrasting
confidence: 75%
“…Therefore, we expect a significant degree of substructure in clusters of galaxies if the remnants of the accretion of groups in the recent past has not been erased by the dynamical relaxation of the clusters. The substructure in rich clusters has been extensively analyzed in recent years (Dressler & Shectman 1988;West & Bothun 1990;Zabludoff et al 1993;Girardi et al 1997;Solanes, SalvadorSolé, & Gonzáles-Casado 1999). The results are consistent with substructure in most of the cases studied, irrespective of the samples and method of analyses used.…”
Section: Introductionmentioning
confidence: 99%
“…According to the present data sets, it is unlikely that there are significant differences between the two mass estimators. The virial masses are from Carlberg et al (1996) and Girardi et al (1997a).…”
Section: Discussionmentioning
confidence: 99%
“…This cluster is at z = 0.0205; its internal structure is not clearly understood. Girardi et al (1997) found that it consists of two systems, both very extended, separated in velocity by over 4000 km s −1 , but spatially overlapping. The BCG in the NVSS image is not detected (≤1.4 mJy), which corresponds to an upper limit to the total power of Log P ≤ 21.1 (W/Hz).…”
Section: Notes On Individual Sourcesmentioning
confidence: 98%
“…It is a highly structured cluster despite the apparently regular velocity distribution of the main field. This cluster should be considered as an ongoing cluster merging (Girardi et al 1997). This cluster exhibits two peaks in the X-ray emission (Bird et al 1995).…”
Section: Notes On Individual Sourcesmentioning
confidence: 99%